Pembelajaran Komunikasi, Motivasi Dan Muhasabah Untuk Guru, Siswa Dan Mahasiswa Di Masjid Al Muhajirin Perum Telaga Harapan Cikarang Barat Kabupaten Bekasi - Saktisyahputra Saktisyahputra (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2018)
Learning communication and motivation of a teacher, student and student is one of the important components in the teaching and learning process. This skill development should be possessed by a teacher, student and student by involving various community activities with Communication Skill and Motivation.Carrying the theme "Communication, Motivation And Student Learning For Teachers, Students And Students". The aim is to train and equip skills and improve communication skills and effective motivation to improve the quality of human resources for teachers, students and students in West Cikarang, Bekasi Regency, West Java.Based on interviews, questions and answers and direct observations during the activity, community service activities give the following results: (1). Increased knowledge and understanding of participants in having effective communication and motivation skills, (2). Increased the skills of participants in building togetherness (Chemistry) inside or outside their duties as teachers, students and students.